The Functional Psychotherapy Approach: A Process-Outcome Multiple Case Study - Rocco, Diego; Rizzi, Luca; Dell’Arciprete, Gaia; Perrella, Raffaella (Frontiers in Psychology, 2022)
Abstract Objective: The present work aims to conduct a first naturalistic empirical analysis on the process and outcome assessment of the Functional Psychotherapy (FP) intervention treatment, a model of psychotherapy that has its roots in psychoanalysis and integrates the verbal communication approach founded on transference and countertransference dynamics with the analysis of bodily processes. Method: The research’s sample included ten patients, who joined the study on a voluntary basis and were met by clinicians in their private practices. Each patient received a FP with an average duration of 40 hours (min 35, max 42). Therapies had weekly sessions, were audio-recorded with the patients’ written consent, and lasted for an average of 10 months (from 9 to 12). Different outcome and process tools were applied: the Minnesota Multiphasic Personality Inventory-2 (MMPI-2) and the Luborsky’s the Core Conflictual Relationship Theme (CCRT) were applied to verify the therapies’ outcomes; the Metacognition Assessment Scale (MAS) and the Italian Discourse Attributes Analysis Program (IDAAP) system were applied to evaluate both the therapies’ outcome and process. MMPI-2 was used also in the follow up. Results: Results highlight that FP has a positive outcome on the patients considered in this study, and that the results were maintained over time. Some specific features of the FP approach emerged through the analysis of the therapeutic processes; these features have been related to the positive outcome obtained. Conclusion: The work constitutes a first step toward an analysis of the therapeutic effectiveness of FP. Future developments shall apply the methodology to a larger sample, possibly introducing different methodologies which allow to detect the specific bodily oriented processes and techniques.